Can Active Labor Market Policy Be Counter-Productive? - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2014)
We study active labor market policies (ALMP) in a matching model. ALMPs are modelled as a subsidy to job search. Workers differ in their productivity, and search takes place along an extensive margin. An additional job seeker affects the quality of unemployed workers. As a result, the Hosios conditions are no longer valid. To replicate the optimum the worker share in bargaining must exceed the Hosios level, and one must impose a tax on job search activity. The coalition in favor of ALMP is also studied.
Keywords: E24; J6; 330; active labor market policy; matching models